Stabbings and safeguarding in children and young people: a local re-audit 2009-2011. (24th May 2012) - Armitage, AJ; Apps, JR; Sutcliffe, A; Cheetham, M; Bangalore, S; Cummins, M
Abstract : Aims: A recent pan-London audit on paediatric stabbings and child protection between March 2007-March 2009 (J R Apps et al, presented at RCPCH Annual Meeting 2011) showed this to be a significant presentation across 20 London hospitals and that documented referrals to the police and social services were low. Following changes in GMC guidelines regarding knife wound presentations, effective from September 2009, it is now mandatory to inform the police and there is increased emphasis on child protection concerns. This study aimed to re-audit management of paediatric stabbing attendances to a London Emergency Department following the change in GMC guidelines and the local introduction of a system for notification of the police direct from A&E reception (effective from September 2009). Methods: The Symphony system was searched for all attendances under-18 years with "stabbing" or "assault with sharp object" from March 2009-March 2011. Attendances were analysed by characteristics of attack, patient demographics, rates of referral to police and social services and involvement of the paediatric team. Outcomes were compared to local data collected for the previous pan-London Audit. Results: In total there were 39 presentations, with 20 cases in under-16 year olds. 10 (26%) had more than one site of injury, 12 (31%) were admitted and 3 (8%) required surgery. Of those discharged direct from A&E (27 in total), there was documented notification of parents for 14 patients (52%), social services for 4 (15%) and the police for 23 (85%, improving to 96% after September 2009). Among all patients, 10 (26%) had another separate presentation with stabbing and 19 (49%) with assault recorded on Symphony. Conclusions: Rates of stabbing presentations in under 18s remain high. For the hospital in question there was significant improvement in documented rates of referral to the police and some improvement in rates of involvement of social services, parents and the paediatric team. There continues to be substantial rate of re-presentation with stabbing or assault following a stabbing suggesting scope for intervention that may decrease future rates of presentation.